2023
DOI: 10.1063/5.0163806
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning enhanced droplet microfluidics

Claire Barnes,
Ashish R. Sonwane,
Eva C. Sonnenschein
et al.

Abstract: Machine learning has recently been introduced in the context of droplet microfluidics to simplify the process of droplet formation, which is usually controlled by a variety of parameters. However, the studies introduced so far have mainly focused on droplet size control using water and mineral oil in microfluidic devices fabricated using soft lithography or rapid prototyping. This approach negated the applicability of machine learning results to other types of fluids more relevant to biomedical applications, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
2
1
0
Order By: Relevance
“…We observed that the droplet length L normalized by the width of the droplet generation area w was inversely proportional to the capillary number of the continued phase, defined as Ca c = μ c U c /γ, where μ c is the shear viscosity, γ is the interfacial tension, and U c is the velocity of the continuous phase calculated as U c = Q c / hw , where h is the height of the microfluidic device (Figure b). When increasing the value of Ca c , which practically meant an increase of Q c in each microfluidic device, the droplet size decreased, in agreement with previous observations. , Similarly, we observed that an increase in the flow rate ratio Q d / Q c resulted in the formation of elongated droplets (Figure c). This behavior is because larger Q d values require larger values of Q c to keep the droplet size constant .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that the droplet length L normalized by the width of the droplet generation area w was inversely proportional to the capillary number of the continued phase, defined as Ca c = μ c U c /γ, where μ c is the shear viscosity, γ is the interfacial tension, and U c is the velocity of the continuous phase calculated as U c = Q c / hw , where h is the height of the microfluidic device (Figure b). When increasing the value of Ca c , which practically meant an increase of Q c in each microfluidic device, the droplet size decreased, in agreement with previous observations. , Similarly, we observed that an increase in the flow rate ratio Q d / Q c resulted in the formation of elongated droplets (Figure c). This behavior is because larger Q d values require larger values of Q c to keep the droplet size constant .…”
Section: Resultssupporting
confidence: 92%
“…When increasing the value of Ca c , which practically meant an increase of Q c in each microfluidic device, the droplet size decreased, in agreement with previous observations. 27 , 28 Similarly, we observed that an increase in the flow rate ratio Q d / Q c resulted in the formation of elongated droplets ( Figure 2 c). This behavior is because larger Q d values require larger values of Q c to keep the droplet size constant.…”
Section: Resultssupporting
confidence: 68%
“…The droplet (formation) mechanism and also the internal reaction environment are complex and controlled by numerous conditional parameters such as surface tension, viscosity of two immiscible liquids, surface wetting properties, inertia, elasticity, and surfactant addition. However, in recent years, machine learning (ML) and artificial intelligence (AI) have begun to be used for parameter optimization as a data-driven study [20].…”
Section: Introductionmentioning
confidence: 99%